What factors influence clinical nurses' self-efficacy after wound care training? A scoping review - Rosdiana Saniapon; Kuswantoro Rusca Putra; Dina Dewi Sartika Lestari Ismail; Retno Lestari (PAGEPress Publications, 2024)
The inadequate management of wounds carries significant implications for patients and challenges clinical nurses. Consequently, there is a need for wound care training to enhance self-efficacy. However, despite participation in such training, nurses often need more practical experience and educational background to exhibit higher confidence levels. This results in a deficiency in self-efficacy when performing wound care. This study aims to amalgamate literature discussing the determinants influencing self-efficacy and present strategies for clinical nurses to enhance it after wound care training. The article search utilized the PRISMA method, with searches conducted in Google Scholar, Proquest, Science Direct, and Pubmed databases. Sixteen articles met the specified inclusion criteria, which required English-language articles published within the last five years (2018-2023) discussing factors affecting clinical nurse self-efficacy after wound training. Various factors, including competence, social support, and self-motivation, influence wound nurses' self-efficacy. Competence factors encompass structured training and education, while social support involves sharing experiences and engaging in case reflection. Additionally, motivational factors play a significant role, such as reinforcing values and attitudes when facing obstacles and maintaining the belief that nurses can effectively adhere to wound care standards. Enhancing self-efficacy includes improving competencies through standardized wound training, increasing educational opportunities, self-experience, social persuasion support, sharing experiences, high self-motivation, and managing emotions when assessing one's ability to achieve goals successfully. Professional development programs designed to provide structured training for nurses have enhanced their competencies, social support, and motivation, strengthened holistic wound care clinical skills and improved self-efficacy. Therefore, exploring additional factors that may further contribute to this positive outcome is advisable.